Gestational risks determinants of mothers of newborns in neonatal death (Acta Scientiarum. Health Sciences, 2015)
Describes the socio-economic, reproductive and obstetric characteristics of mothers of newborn children that had neonatal death in Londrina, Paraná State, Brazil. The quantitative descriptive retrospective research is based on data retrieved from the declaration of live birth, death certificate and infant death investigation form, between 2000 and 2009. During a period of 10 years, 537 newborn children died; 50.5% of mothers were nulliparous; 60.0% were between 12 and 27 years old; 30.8% had less than seven years of schooling; 55.2% had an income of more than two minimum wages. Over 90.0% of mothers had previous history of infant death prior to pregnancy. Further, 91.4% attended prenatal courses and all of them showed some type of disease during pregnancy which, in most cases, led to the death of the newborn child in the early neonatal period (p